2011
DOI: 10.1182/blood-2011-03-339945
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a comparison of nonmyeloablative allografting with autografting for newly diagnosed myeloma

Abstract: Before the introduction of new drugs, we designed a trial where treatment of newly diagnosed myeloma patients was based on the presence or absence of HLAidentical siblings. First-line treatments included a cytoreductive autograft followed by a nonmyeloablative allograft or a second melphalan-based autograft. Here, we report long-term clinical outcomes and discuss them in the light of the recent remarkable advancements in the treatment of myeloma. After a median follow-up of 7 years, median overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 37 publications
7
107
3
2
Order By: Relevance
“…17,18,21 They are, however, worse than those for patients undergoing upfront RIC allo-SCT, which is not unexpected, given the prolonged disease history and more extensive prior therapies. [4][5][6][7][8][9][10][11][12] Although the relatively high NRM that we observed has to be taken into consideration, the data presented in this manuscript show that CMV-seronegative patients who have a CMV-seronegative donor have a substantially reduced NRM that translates into an encouraging 5-year survival of 440%. Considering that almost half (44.6%) of the patients in this study had undergone two or more prior autografts, our findings provide support to the notion that RIC allo-SCT can be an effective treatment option for some heavily pretreated patients.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…17,18,21 They are, however, worse than those for patients undergoing upfront RIC allo-SCT, which is not unexpected, given the prolonged disease history and more extensive prior therapies. [4][5][6][7][8][9][10][11][12] Although the relatively high NRM that we observed has to be taken into consideration, the data presented in this manuscript show that CMV-seronegative patients who have a CMV-seronegative donor have a substantially reduced NRM that translates into an encouraging 5-year survival of 440%. Considering that almost half (44.6%) of the patients in this study had undergone two or more prior autografts, our findings provide support to the notion that RIC allo-SCT can be an effective treatment option for some heavily pretreated patients.…”
Section: Discussionmentioning
confidence: 69%
“…27 However, previously published studies investigating allo-SCT in MM have not analysed the impact of CMV serostatus on outcome. [5][6][7][8][9][10][11]22,28,29 Primary infection or re-activation can occur in CMV-seropositive recipients and recipients of grafts from seropositive donors. The availability of sensitive monitoring methods for the detection of CMV reactivation, combined with pre-emptive anti-CMV therapy, Abbreviations: Auto-SCT ¼ autologous SCT; CI ¼ confidence interval; NRM ¼ non-relapse mortality; RIC allo-SCT ¼ reduced intensity-conditioned allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a median follow-up of 7 years, the median OS was not reached (P = 0.02) and PFS was 39 months (P = 0.02) in the 58 patients who received an allo-SCT, whereas OS was 5.3 years and EFS 33 months in the 46 who received tandem ASCT. 32 In those achieving CR after allotransplant, 53% were in continuous complete remission compared with 19% for CR following tandem ASCT. This was the first randomized study that showed an advantage for allo-SCT over ASCT in MM and indicated that CR achieved after allotransplant was durable with a plateau in Abbreviations: Bu = busulfan; cGVHD = chronic GVHD; Cy = cyclophosphamide; EBMT = European Bone Marrow Transplantation; HOVON-24 = HaematoOncology Foundation for Adults in the Netherlands-24; m = months; Mel = melphalan; N/R = not reported; OS = overall survival; TRM = treatment-related mortality; y = years.…”
Section: Non-myeloablative/reduced-intensity Conditioningmentioning
confidence: 99%
“…However, relapse of multiple myeloma is still a major concern after alloHSCT. 1,2 Whilst ocular involvement in chronic GVHD (cGVHD) is a frequent complication after alloHSCT, 3 ocular involvement by multiple myeloma is rare. 4 Here, we report a case of a 42-year-old male patient who presented with isolated orbital relapse of multiple myeloma during treatment of severe ocular cGVHD.…”
mentioning
confidence: 99%